2000
DOI: 10.1163/156854100508953
|View full text |Cite
|
Sign up to set email alerts
|

The effect of artificial substrates on the pathogenicity of Steinernema feltiae (Rhabditida: Steinernematidae) to adult Musca domestica (Diptera: Muscidae)

Abstract: Effects of some artificial substrates on the ability of the entomopathogenic nematode Steinernema feltiae to kill adult Musca domestica were studied. Replicate samples of different substrates were treated with known numbers of S. feltiae suspended in 0.25 M sucrose. Then 30 adult female flies were confined above each sample in a crystalizing basin and mortality counts were carried out 48 h later. The most effective substrates were poplin cotton, potting compost, silver sand and Fibertex SF250 horticultural cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Other types of animal manure also generally are not as nitrogen-rich as that of poultry, and the entomopathogenic nematodes may have better prospects there. If used in a bait station type approach, the porosity of substrate can have substantial effects on how well flies may be infected by such nematodes; cotton poplin was good, while Perlite was poor, for example (Renn and Wright, 2000).…”
Section: Nematodesmentioning
confidence: 99%
“…Other types of animal manure also generally are not as nitrogen-rich as that of poultry, and the entomopathogenic nematodes may have better prospects there. If used in a bait station type approach, the porosity of substrate can have substantial effects on how well flies may be infected by such nematodes; cotton poplin was good, while Perlite was poor, for example (Renn and Wright, 2000).…”
Section: Nematodesmentioning
confidence: 99%
“…In contrast, mortality was <70% when flies were housed with pads moistened with an EPN-based suspension in 5% sucrose, even at the high rate of 100,000 EPN per ml of bait. Renn and Wright (2000) found that EPN delivery in a 0.25 M sucrose solution to adult flies varied depending on the type of substrate on which the bait was presented. For example, the lethal dose to 50% mortality (LD 50 ) for S. feltiae was about 200 times lower on cotton poplin than on perlite.…”
Section: House Fliesmentioning
confidence: 99%